Optimization of solid state fermentation parameters for bioethanol production from waste glycerol using immobilized escherichia coli - Chilakamarry, Chaitanya Reddy (2022)
The rapid industrial and economic development runs on fossil fuels and other energy sources. Limited oil reserves, environmental issues, and high transportation costs lead towards carbon unbiased renewable and sustainable fuel. Compared to other carbon-based fuels, biodiesel is attracted worldwide as a biofuel to reduce global dependence on fossil fuels and the greenhouse effect. During biodiesel production, approximately 10% of glycerol is formed as byproduct. Malaysia is one of the largest producers of palm oil in the global market; thus, palm oil is used as the primary source for biodiesel production. In Malaysia, 480 million liters of biodiesel was produced in 2017 and is expected to reach 815 million liters in 2027, showing a 66% increase. Valorizing industrial waste is a big challenge to provide a significant economic advantage through the sustainable approach. Hence, there is an urgent need to find a compromising way to balance the environmental protection and sustainable reuse of the glycerol residue from the biodiesel industry. Our present work aims to produce bioethanol from biodiesel waste using immobilized Escherichia coli cells by solid-state fermentation. Hence, glycerol waste from the biodiesel industry is used as the carbon source for bioconversion to ethanol without primary treatment using Escherichia coli. Escherichia coli cells were immobilized using Na alginate. The stability, leakage and recycling of immobilized cells were studied for solid-state fermentation. High-performance liquid chromatography was used to analyze the concentration of glycerol and ethanol. Fourier transform infrared spectroscopy was used to analyze the functional group of glycerol and ethanol. Ethanol that has been produced was optimized by Response Surface Methodology. The important bio-process parameters such as inoculum (20%), mass substrate (20 g) and time (12 h) optimized to achieve maximal ethanol production of 10.0 g/L by immobilized E.coli cells. The kinetic study of free cells and immobilized cells were studied. The results obtained for maximum specific growth rate μmax was 0.028 h-1 and KS 6.23 g obtained for immobilized cells, while for the free cells, maximum growth rate μmax was 0.025 h-1 and KS of 5.11g. This study successfully used the biodiesel byproduct waste glycerol as the carbon source for the fermentation, using immobilized E.coli cells to produce ethanol.